Molecular design, synthesis and in vitro biological evaluation of thienopyrimidine-hydroxamic acids as chimeric kinase HDAC inhibitors: a challenging approach to combat cancer - Mona M. Abdel-Atty; Nahla A. Farag; Rabah A. T. Serya; Khaled A. M. Abouzid; Samar Mowafy (Taylor & Francis Group, 2021)
A series of thieno[2,3-d]pyrimidine-based hydroxamic acid hybrids was designed and synthesised as multitarget anti-cancer agents, through incorporating the pharmacophore of EGFR, VEGFR2 into the inhibitory functionality of HDAC6. Three compounds (12c, 15b and 20b) were promising hits, whereas (12c) exhibited potent VEGFR2 inhibition (IC50=185 nM), potent EGFR inhibition (IC50=1.14 µM), and mild HDAC6 inhibition (23% inhibition). Moreover, compound (15c) was the most potent dual inhibitor among all the synthesised compounds, as it exhibited potent EGFR and VEGFR2 inhibition (IC50=19 nM) and (IC50=5.58 µM), respectively. While compounds (20d) and (7c) displayed nanomolar selective kinase inhibition with EGFR IC50= 68 nM and VEGFR2 IC50= 191 nM, respectively. All of the synthesised compounds were screened in vitro for their cytotoxic effect on 60 human NCI tumour cell lines. Additionally, molecular docking studies and ADMET studies were carried out to gain further insight into their binding mode and predict the pharmacokinetic properties of all the synthesised inhibitors.